The Denial of Polygamy as the Excuse for Men's Sexual Desire - Nurul Aminah, Ubaidah (Jurnal Perempuan dan Anak, 2023)
Marriage is a very interesting issue to discuss. Islam allows men to have more than one wife or what is commonly known as polygamy. Polygamy reaps many pros and cons, because many people abuse the permissibility of polygamy. Many women reject polygamy. They are afraid that there will be injustice in the household because their husband is just an ordinary human being. Besides that, there have been many mistakes in polygamy, namely women are used as gratification for the lust of irresponsible Adam. This writing aims to find out the make polygamy rejected and education regarding the problems of polygamous Adams only make women as gratification. The method used by the author in this research is literature study. The data in this study were analyzed using descriptive analysis. This research shows that polygamy was originally carried out as a form of protection for widows, orphans, and the embodiment of the mission of justice and humanity. In fact, the men practice polygamy as a form of gratification under the umbrella of religion. Women seeing this fact reject practice of polygamy, but this refusal does not mean forbidding what is permissible. Under the guise of getting great rewards and following the sunnah, many are found to be reasons for men to practice polygamy. When in fact lust and desire drive them to polygamy. Rejecting the practice of polygamy as a means of satisfying the desires of Adam is not something that prohibited, because such polygamy brings many harms to women.